(untitled) (Journal of Green Business School, 2025)
This study’s main goal is to find out how working capital financing affects the earning power of private commercial banks that operate in Bangladesh. Five private commercial banks are chosen because they have sufficient data and yearly audited financial reports covering the years 2014 to 2023. Descriptive statistics, multiple linear regressions, and the Pearson correlation coefficient are used to analyze the data. The independent elements are the size of the bank (total assets), increase in operational income, leverage ratio, and working capital financing. The dependent variable is the return on equity. The findings show a strong relationship between working capital financing and the earning power of the private commercial banks in Bangladesh that were included in the sample. Furthermore, the sample features have a major influence on the profitability ratios of the sample private commercial banks. In the end, negative indicators of each of the chosen variables for NBL points to poor working capital management, which lowers profitability. To enhance their profits, the private commercial banks in the sample need to keep a tight eye on loan disbursement, working capital disbursement, loan recovery and advances, an effective method for managing expenses, and the right amount of assets. J. of Green Business. Sch. Vol 6(1), Jan-Dec, 2023; pp 98-115